Derek Jarman : le peintre à la caméra - Nicole Cloarec (Itinéraires)
In what way can Derek Jarman’s work help us question the relationships between painting and cinema beyond mere quotations? Given that both his pictorial and filmic works display the same thematic and formal preoccupations, this article examines how pictorial issues infuse his films, in particular through two main questions in art history, first the dichotomy between surface and depth, second, the tension between figuration and abstraction. In both cases, the questions are conveyed in filmic terms through the use of light and colour, resulting in two seemingly opposite aesthetic trends, from austere monochromes to flamboyant superimpositions and montage. The pictorial question thus enables us to understand how these two trends are part and parcel of the same filmic poetics, characterised by non-realism and a desire to explore the limits of representation. Film is no longer considered a mere photographic support to print but a genuine pictorial support to shape.